Freud, Jung and The Great Chain of Being - Ekstrom, Soren (Journal of analytical psychology, 2018)
For some time, it has been clear that psychoanalytic theories are built upon the kind of master narratives Roy Schafer, a New York psychoanalyst, described in 1980. As such, psychoanalytic theories may today have lost some of their initial scientific credibility in that they can no longer be seen as summarizing findings from data collected in a research environment. As aids in participating in their patients’ process of healing, however, narratives continue to be used by practitioners and reflect allegiance to core beliefs and propositions with roots in long-standing Western thought. In this article, the metaphors in master narratives of Freud and Jung are compared with a conceptual system identified by cognitive linguists as ‘The Great Chain of Being’. Based on this analysis, the article proposes that theoretical formulations have mainly a secondary role to play in achieving good outcomes. The most critical element is the therapist’s capacity to access a specific narrative for what transpires throughout each treatment.